Influence Of Membrers Participation And Micro Enterprises On Success Of Kud Argopuro - Anisatul Magfiroh, Tutik (FORAGRI : Jurnal Ilmu Pertanian, 2021)
Probolinggo has highest contribution toward East Java Province in milk production. It was in 3rd ranked in milk production and also contributed for 0.724% toward national level. Farmer’s interest in joined-to-cooperation showed a good trend especially in Argopuro Cooperation. It can be seen from increasing trend of registered member in Argopuro Cooperation from 1.131 members to 3502 members in 2015. This member’s increasing might be influenced by some assistances with SPI program. The SPI program helped the new farmer member candidate by giving a six years-old fresh calf.. In spite of these assistances, calf farmer has low participation to join with Argopuro Cooperation. This study was aimed to determine: 1) the effect of member’s participation toward successfulness in Argopuro Cooperation. 2) effect of member’s participation with support of business environment variable toward successfulness in Aropuro Cooperation. This study was held purposively in Krucil with member population for 3502 and distributed around three main villages. The members were selected by using simple cluster sampling among 63 members from population member. The data was analyzed by using effect variable analysis. There are two regression models in this study. First model attempted to determine the effect of member’s participation toward successfulness. The last model tried to reveal the effect of member’s participation toward successfulness which was supported by business environment variable. The result showed that (1) member’s participation has significant and positive effect toward successfulness of Argopuro Cooperation for 0.739; (2) member’s participation with support of business environment variable has significant and positive effect toward successfulness in Argopuro Cooperation for 0.015.